Iron-Promoted Decarboxylation of Arylacetic Acids for the Synthesis of Aromatic Nitriles with Sodium Nitrite as the Nitrogen Source - Shen, Zhenpeng; Liu, Wenbo; Tian, Xinzhe; Zhao, Zhe; Ren, Yun-Lai (Synlett, 2020)
A new and effective method was developed for the synthesis of aromatic nitriles from arylacetic acids by using NaNO2 as the nitrogen source and Fe(OTf)3 as the promoter at 50 °C. A series of arylacetic acids underwent this transformation to give the targeted products in yields of 51–90%. Because of the mild conditions, the reaction is compatible with a broad range of functional groups, including ester, carboxy, hydroxy, acetamido, halo, nitro, cyano, methoxy, and even highly reactive formyl groups.
Keywords: aryl nitriles; nitriles; decarboxylation; sodium nitrite; iron catalysis; arylacetic acids